(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Advances in reprogenetic tools have completely changed parents’ previously passive role in deciding what characteristics their children will have, giving rise to significant bioethical and legal implications. They now have genetic information which they can use in their reproductive decision-making to avoid serious disease in their children. Thus, children might bring claims against their parents, not only for their actions but also for their omissions. Therefore, this paper discusses whether parental freedom jeopardizes the rights of children and future generations. It discusses various conflicting and introduces the current legal discourse around the feasibility of CRISPR-Cas9 lawsuits.